Exploring Ethical Issues in the Gulf Cooperation Council Construction Industry: Comparing the Sultanate of Oman and the United Arab Emirates - Hilal Ali Salim Al Issai; Abdullahi A. Umar; Atef Badr (Journal of Construction in Developing Countries, 2026)
Since the early phases of the Gulf Cooperation Council’s (GCC) rapid development, media reports have frequently raised concerns about unethical practices within the construction industry. However, empirical evidence identifying the prevalence of these ethical issues remains elusive. This exploratory study addresses the gap with a focus on ethical challenges in the Sultanate of Oman and the United Arab Emirates (UAE). A survey conducted among construction professionals in both countries resulted in a total of 357 respondents. Exploratory factor analysis with Monte Carlo principal component analysis (PCA) for parallel analysis identified fraud, delayed payments, contractor misrepresentation, intimidation, tax avoidance and discrimination as significant ethical concerns. Independent samples t-tests revealed no statistically significant difference between the two countries, suggesting the findings to be broadly similar within the contexts of the two countries. The findings suggest that policymakers reform public procurement systems and enforce strict conflict-of-interest mechanisms. Academic institutions can contribute by developing mandatory stand-alone engineering ethics modules in undergraduate engineering courses. Similarly, professional engineering institutions should integrate ethics training into continuing professional development activities. Though exploratory in nature, the study provides an overview of the ethical challenges in the construction industries in both Oman and the UAE.